2017
DOI: 10.1002/asi.23877
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic reranking of biomedical search results based on extracted entities

Abstract: Health-related information is nowadays accessible from many sources and is one of the most searched-for topics on the Internet. However, existing search systems often fail to provide users with a good list of medical search results, especially for classic (keyword-based) queries. In this article we elaborate on whether and how we can exploit biomedicine-related entities from the emerging Web of Data for improving (through reranking) the results returned by a search system. The aim is to promote relevant but lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Future research may exploit it to further improve the efficiency of the proposed framework. In [50], a bipartite graph is generated between top retrieved documents and entities extracted from the documents to measure entity importance of the candidate entities, and those importance scores were used to re-rank the initial search results. Although we focus more on query extension rather than on re-ranking, this graph-based approach can still be adapted to extract candidate terms from the knowledge structure additionally by measuring the term importance as well as co-occurrences of the terms.…”
Section: Discussionmentioning
confidence: 99%
“…Future research may exploit it to further improve the efficiency of the proposed framework. In [50], a bipartite graph is generated between top retrieved documents and entities extracted from the documents to measure entity importance of the candidate entities, and those importance scores were used to re-rank the initial search results. Although we focus more on query extension rather than on re-ranking, this graph-based approach can still be adapted to extract candidate terms from the knowledge structure additionally by measuring the term importance as well as co-occurrences of the terms.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we propose a biased (personalized-like) PageRank algorithm for analyzing the graph and scoring its nodes. Similar modeling and scoring methods have been applied for the problems of results re-ranking [13] and enrichment [12] in information retrieval.…”
Section: Stochastic Modelingmentioning
confidence: 99%
“…Advancing Information Retrieval. Recent works have shown that the exploitation of entities extracted from search results can enhance the effectiveness of keywordbased search systems in different contexts, like in biomedical [12] and academic [50] search. Consequently, a semantic layer built on top of a collection of archived documents can also serve a search system operating over the same collection.…”
Section: Other Exploitation Scenariosmentioning
confidence: 99%